Trends of development of higher education in Russia: opportunities or threats? (Путеводитель предпринимателя)
In the article the main documents defining functioning of system of higher education of Russia are analysed. The main trends ofdevelopment of higher education, having mainly subjective basis are defined. Following such trends will promote loss of the accumulated experience of pedagogical shots and, as a result, decrease in innovative capacity of higher education institutions.